2022
DOI: 10.3390/genes13061055
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic Prioritization and Functional Annotation of GWAS-Based Candidate Genes for Primary Open-Angle Glaucoma

Abstract: Background: Primary open-angle glaucoma (POAG) is the most prevalent glaucoma subtype, but its exact etiology is still unknown. In this study, we aimed to prioritize the most likely ‘causal’ genes and identify functional characteristics and underlying biological pathways of POAG candidate genes. Methods: We used the results of a large POAG genome-wide association analysis study from GERA and UK Biobank cohorts. First, we performed systematic gene-prioritization analyses based on: (i) nearest genes; (ii) nonsyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 119 publications
3
7
0
Order By: Relevance
“…That is, RAR alpha caused significant reductions in vascular leakage in the diabetic retina by antagonizing the loss of tight junction integrity that is induced by diabetes [ 38 ]. These observations corresponded well with our current results, which show that ATRA exerts synergistic and beneficial effects in TGF-β2-treated 2D- and 3D-cultured HTM cells; our results were found through in vitro models that replicate the single- and multiple-sheet barrier structures of the HTM [ 25 , 26 , 39 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…That is, RAR alpha caused significant reductions in vascular leakage in the diabetic retina by antagonizing the loss of tight junction integrity that is induced by diabetes [ 38 ]. These observations corresponded well with our current results, which show that ATRA exerts synergistic and beneficial effects in TGF-β2-treated 2D- and 3D-cultured HTM cells; our results were found through in vitro models that replicate the single- and multiple-sheet barrier structures of the HTM [ 25 , 26 , 39 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 92%
“…Unexpectedly and interestingly, the addition of ATRA significantly suppressed the TGF-β2-induced enhancement in TEER values ( Figure 1 ). Since it was suggested that ATRA greatly affected mitochondrial functions [ 26 ] as well as glycolysis [ 27 ], we next investigated the issue of whether or not ATRA had any effects on TGF-β2-untreated and -treated 2D HTM cells. Interestingly, such discordant effects of ATRA between TGF-β2-untreated and -treated 2D HTM cells were also observed by a real-time cellular metabolic analysis using a Seahorse bioanalyzer ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In MON, but not UON, further downstream partners of p53 that were upregulated included Serpine1 and Thbs1 , suggesting an effect of inhibiting angiogenesis. One genome wide association study found a relation between a p53 polymorphism and one human glaucoma phenotype[34], while another found KEGG pathways associated with human open angle glaucoma were focal adhesion, and Wnt and TGFβ signaling, strikingly similar to the naïve UON pathways active in our study [35].…”
Section: Discussionsupporting
confidence: 76%
“…In MON, but not UON, further downstream partners of p53 that were upregulated included Serpine1 and Thbs1, suggesting an effect of inhibiting angiogenesis. One genome-wide association study found a relation between a p53 polymorphism and one human glaucoma phenotype [34], while another found KEGG pathways associated with human open-angle glaucoma were focal adhesion, and Wnt and TGFβ signaling, which are strikingly similar to the naïve UON pathways active in our study [35].…”
Section: Discussionsupporting
confidence: 72%